The Communication between God and Demons (An Analysis of Thematic Interpretation of Fi Zilal Al Quran) - Kholil, Syukur; Arifin, Zainal; Muniruddin, Muniruddin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Aim of this study was (1) to know how the process of communication between God with Demons, according to Ulama, (2) to know the themes of communication between God with Demons according thematic interpretation fi zilal al Quran, (3) to know what got from communication between God with Demons according in thematic interpretation fi zilal al Quran. The method was the qualitative of descriptive approach, based on the thematic interpretation of communication, where verses realated to communication between God with Demons, divided to six categories, then was studied according to Ulama and interpretation fi zilal al Quran. Subject of the study was based on al Quran and Tafsir fi zilal al Quran by al Syahid Sayyid Quthb. Object of the study was what and how type and theme of communication between God with Demons version thematic interpretation fi zilal al Quran. Technique for data collection were document and data analysis in sorting and choosing data to goal of study. The result of this research was (1) process of communication between God with Demons in Tafsir fi zilal al Quran felt harmonic and to be i’tibar to Creature, Demons, and Human, (2) There were six themes of communication between God with Demons, (3) There were six studies from communication between God with Demons.